Condyle-Specific Matching Does Not Improve Midterm Clinical Outcomes of Osteochondral Allograft Transplantation in the Knee. (4th October 2017) - Wang, Dean; Jones, Kristofer J.; Eliasberg, Claire D.; Pais, Mollyann D.; Rodeo, Scott A.; Williams, Riley J.
Abstract : Background: Condyle-specific matching for osteochondral allograft transplantation (OCA) pairs donor and recipient condyles in an attempt to minimize articular incongruity. While the majority of cartilage defects are located on the medial femoral condyle, lateral femoral condyles are more commonly available as a graft source. The purpose of this study was to compare the clinical outcomes of patients treated with non-orthotopic (lateral-to-medial condyle or medial-to-lateral condyle) OCA with those treated with traditional orthotopic (medial-to-medial condyle or lateral-to-lateral condyle) OCA. We hypothesized that clinical outcomes would be similar between groups at midterm follow-up. Methods: A retrospective review of prospectively collected data on patients treated with OCA from 2000 to 2014 was conducted. Seventy-seven patients with a full-thickness cartilage defect of a femoral condyle were treated with either orthotopic (n = 50) or non-orthotopic (n = 27) OCA. A minimum follow-up of 2 years was required for analysis. Patients in each group were matched according to sex, age, and total chondral defect size. Reoperations and patient responses to validated outcome measures were reviewed. Failure was defined as any revision cartilage procedure or conversion to knee arthroplasty. Results: The mean duration of follow-up was 4.0 years (range, 2 to 16 years). The orthotopic and non-orthotopic OCA groups were comparable in terms of demographics, the mean number of prior ipsilateral knee operations, and the percentage of concomitant procedures at baseline. Reoperation (p = 0.427) and failure (p = 0.917) rates did not differ significantly between groups. Both groups demonstrated significant increases in the Short Form-36 (SF-36) physical functioning and pain, International Knee Documentation Committee (IKDC), and Knee Outcome Survey-Activities of Daily Living (KOS-ADL) scores compared with baseline (p < 0.004). Outcome scores (baseline and postoperative) and change scores did not differ significantly between groups. Conclusions: Clinical outcomes do not differ between patients treated with orthotopic OCA and those treated with non-orthotopic OCA, suggesting that condyle-specific matching may not be necessary. Level of Evidence: TherapeuticLevel III . See Instructions for Authors for a complete description of levels of evidence.